2023
DOI: 10.3389/fimmu.2023.1291530
|View full text |Cite
|
Sign up to set email alerts
|

Targeting vascular normalization: a promising strategy to improve immune–vascular crosstalk in cancer immunotherapy

Cheng Qian,
Chaoqun Liu,
Weiwei Liu
et al.

Abstract: Blood vessels are a key target for cancer therapy. Compared with the healthy vasculature, tumor blood vessels are extremely immature, highly permeable, and deficient in pericytes. The aberrantly vascularized tumor microenvironment is characterized by hypoxia, low pH, high interstitial pressure, and immunosuppression. The efficacy of chemotherapy, radiotherapy, and immunotherapy is affected by abnormal blood vessels. Some anti-angiogenic drugs show vascular normalization effects in addition to targeting angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 217 publications
0
1
0
Order By: Relevance
“…It has been observed that lenvatinib inhibits the angiogenic factor in the tumor microenvironment and blocks fibroblast growth factor receptor 4 (FGFR4). This reduces tumor PD–L1 expression and impedes the differentiation of regulatory T cells (Tregs), thereby improving the efficacy of PD–1 antibodies ( 28 , 29 ). The combination of TKIs and PD–1 antibodies presents a favorable therapeutic option for eliminating microsatellite foci that have not yet been detected by imaging ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that lenvatinib inhibits the angiogenic factor in the tumor microenvironment and blocks fibroblast growth factor receptor 4 (FGFR4). This reduces tumor PD–L1 expression and impedes the differentiation of regulatory T cells (Tregs), thereby improving the efficacy of PD–1 antibodies ( 28 , 29 ). The combination of TKIs and PD–1 antibodies presents a favorable therapeutic option for eliminating microsatellite foci that have not yet been detected by imaging ( 30 ).…”
Section: Discussionmentioning
confidence: 99%